Mixed-Embeddings and Deep Learning Ensemble for DGA Classification With Limited Training Data - Christian Morbidoni; Alessandro Cucchiarelli; Luca Spalazzi (IEEE Access)
Recent papers in the cybersecurity research field of Domain Generation Algorithms (DGAs) detection show the increase of performances associated with the introduction of unsupervised neural vectorized representation of domain names in the supervised classification process. In this paper we explore the effectiveness of this approach by proposing a novel mixed pre-trained neural embeddings model which integrates different vectorized representations of domain names: n-grams streams and words. We used the embeddings with two different classifiers, both based on ensemble architectures: a stacking model and an end-to-end multi-input neural architecture. We trained and tested the classifiers with two datasets, differing both in the distribution of domain names between real and DGAs and in the number and type of DGAs. The obtained results show that our solution provides considerable advantages with respect to state-of-the-art single classifiers both in classification accuracy and in the detection of challenging DGAs, such as those based on word dictionaries. The improvement of performance is significant in a particularly relevant operating condition, known as few-shot-learning, where only few examples of DGA-generated domain names are available for the classifier training.